Factors Associated with The Incidence of Low Birth Weight - Eka Rati Astuti (Journal of Health Science and Prevention, 2021)
Low birth weight (LBW) is one of the causes of infant mortality. LBW babies can be caused by internal and external factors. This research aims to determine the factors associated with the incidence of low birth weight. This research is a retrospective study with a case control approach. The population is all mothers who gave birth in Puskemas Kayu Kunyit in South Bengkulu Regency throughout 2019, as many as 129 people, consisting of 14 babies with LBW and 115 babies with normal birth weight. The sample of this study was 28 people consisting of 14 babies who experienced LBW and 14 babies who were not LBW. Secondary data were obtained from maternal cohort and infant cohort and cases of data the incidence of low birth weight and the risk of pregnant women. Analysis of data using statistical test Chi-Square with a 95% confidence level. The analysis shows that the factors of low birth weight are maternal age (?=0.002), maternal parity (?=0.006), and pregnancy distance (?=0.02). In conclusion, factors associated with the incidence of low birth weight are maternal age, maternal parity, and pregnancy distance in the Puskesmas Kayu Kunyit.